Men of Steel - Sanghvi , Vir; Kaur, Jasmine (Gyan Management Journal, 2011)
This book is a collection of in-depth profiles of the eleven India's biggest business barons. These are the men who are powering new India's leap into the twenty first century - the faces behind the great Indian success story. You'll find them all here, the traditional big names of Indian industry: Ratan Tata and Kumar Mangalam Birla; the new gurus of information technology: Nandan Nilekani and Azim Premji; the wizards of the sunrise entertainment and telephony sector: Sunll Bharati Mittal, Subhash Chandra and Rajeev Chandrasekhar ... and many more.Essential to the depth of these profiles is that all these men sat down for hours to tell Vir Sanghvi about their hopes, their dreams and their heartbreaks. These are profiles based on fresh information, direct from the mouths of the men of steel themselves. This book generates a highly readable insight into the new India.
Keywords: Men of Steel; heartbreaks